Phosphorus-Containing Dibenzonaphthanthrenes: Electronic Fine Tuning of Polycyclic Aromatic Hydrocarbons through Organophosphorus Chemistry - Kivala, Milan; Ascherl, Johannes; Neiß, Christian; Vogel, Alexander; Graf, Jürgen; Rominger, Frank; Oeser, Thomas; Hampel, Frank; Görling, Andreas (Chemistry - A European Journal, 2020)
Starting from versatile acridophosphine a concise synthetic route towards a new family of phosphorus-containing polycyclic aromatic hydrocarbons was established. The structural and optoelectronic properties of these compounds were efficiently modulated through derivatization of the phosphorus center. X-ray crystallographic analysis, UV/vis spectroscopic and electrochemical studies supported by DFT calculations identified the considerable potential of these scaffolds for the development of organophosphorus functional materials with tailored properties upon further functionalization.
CRIS-Team Scopus Importer:2020-06-30
Keywords: olefination; phosphorus heterocycles; photochemistry; polycyclic aromatic hydrocarbons